Second opinion in breast pathology: policy, practice and perception. Issue 11 (22nd July 2014) - Geller, Berta M; Nelson, Heidi D; Carney, Patricia A; Weaver, Donald L; Onega, Tracy; Allison, Kimberly H; Frederick, Paul D; Tosteson, Anna N A; Elmore, Joann G
Abstract : Aims: To assess the laboratory policies, pathologists' clinical practice and perceptions about the value of second opinions for breast pathology cases among pathologists practising in the USA. Methods: Cross-sectional data were collected from 252 pathologists who interpret breast specimens in eight states using a web-based survey. Descriptive statistics were used to characterise findings. Results: Most participants had >10 years of experience interpreting breast specimens (64%), were not affiliated with academic centres (73%) and were not considered experts by their peers (79%). Laboratory policies mandating second opinions varied by diagnosis: invasive cancer 65%; ductal carcinoma in situ (DCIS) 56%; atypical ductal hyperplasia 36% and other benign cases 33%. 81% obtained second opinions in the absence of policies. Participants believed they improve diagnostic accuracy (96%) and protect from malpractice suits (83%), and were easy to obtain, did not take too much time and did not make them look less adequate. The most common (60%) approach to resolving differences between the first and second opinion is to ask for a third opinion, followed by reaching a consensus. Conclusions: Laboratory-based second opinion policies vary for breast pathology but are most common for invasive cancer and DCIS cases. Pathologists have favourable attitudes towards second opinions, adhere to policies and obtain them even when policies are absent. Those without a formal policy may benefit from supportive clinical practices and systems that help obtain second opinions.